Panorama das competências digitais dos professores no Novo Ensino Médio em escolas públicas de São Paulo: um estudo sobre o desenvolvimento docente diante das Tecnologias Digitais de Informação e Comunicação (TDIC) - Bianchi, Cintia Santos Tolosa (2023)
This study aimed to comprehend the panorama of Digital Competences among teachers who teach in the New High School (NHS) in public schools in the city of São Paulo. This thesis was organized into three parts: firstly, different social and political meanings reverberating in schools were problematized. To this end, a brief historical overview of education in Brazil and the changes brought about by the New High School (NHS) were presented. In the second part, the implementation of the New High School (NHS) and its implications for the development of Digital Competences among teachers were discussed. Aspects such as curriculum flexibility, organization by knowledge areas, and the possibilities of integrating digital technologies in the educational process were addressed. The third part examined the digital competence of teachers in Brazilian basic education in relation to ICTs, the New High School (NHS), and the occurrence of Covid-19. An exploratory descriptive research design was employed, and two survey e-questionnaires were used as research instruments: the first administered at the beginning of the pandemic, and the second 30 months later. Data collection was based on an evaluative grid divided into three areas of Teacher Digital Competence, specifically focusing on: a) Pedagogical, b) Digital Citizenship, and c) Professional Development. The results demonstrated that teachers were at the Familiarization level (2 out of 5) in terms of Digital Competences, indicating that they had started to become acquainted with and use technologies in their instructional activities, perceiving them more as instructional aids rather than having a significant pedagogical intentionality